Adenosine A1 Receptor-Mediated Attenuation of Reciprocal Dendro-Dendritic Inhibition in the Mouse Olfactory Bulb - Schulz, Kristina; Rotermund, Natalie; Grzelka, Katarzyna; Benz, Jan; Lohr, Christian; Hirnet, Daniela (Frontiers in Cellular Neuroscience, 2018)
It is well described that A1 adenosine receptors inhibit synaptic transmission at excitatory synapses in the brain, but the effect of adenosine on reciprocal synapses has not been studied so far. In the olfactory bulb, the majority of synapses are reciprocal dendro-dendritic synapses mediating recurrent inhibition. We studied the effect of A1 receptor activation on recurrent dendro-dendritic inhibition in mitral cells using whole-cell patch-clamp recordings. Adenosine reduced dendro-dendritic inhibition in wild-type, but not in A1 receptor knock-out mice. Both NMDA receptor-mediated and AMPA receptor-mediated dendro-dendritic inhibition were attenuated by adenosine, indicating that reciprocal synapses between mitral cells and granule cells as well as parvalbumin interneurons were targeted by A1 receptors. Adenosine reduced glutamatergic self-excitation and inhibited N-type and P/Q-type calcium currents, but not L-type calcium currents in mitral cells. Attenuated glutamate release, due to A1 receptor-mediated calcium channel inhibition, resulted in impaired dendro-dendritic inhibition. In behavioral tests we tested the ability of wild-type and A1 receptor knock-out mice to find a hidden piece of food. Knock-out mice were significantly faster in locating the food. Our results indicate that A1 adenosine receptors attenuates dendro-dendritic reciprocal inhibition and suggest that they affect odor information processing.